Double optical gating of high order harmonics from plasma surfaces. (8th September 2021) - Smith, R E; White, E; Gilmore, P M; Dromey, B; Yeung, M
Abstract: Laser driven high harmonic generation from relativistically oscillating plasma surfaces is a promising route to isolated attosecond pulses with high peak brightness. Here we investigate a double optical gating scheme to restrict the emission to only a single, intense, attosecond pulse even with a multi-cycle driving laser. This scheme, which uses a second harmonic field, combined with a pair of counter-rotating circularly polarized laser pulses, leads to more efficient attosecond pulse generation with improved temporal isolation when compared to a single colour polarization gating scheme.